The Changing Role of the State in the Economy : A Historical Perspective - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1997)
This paper discusses the role of the state from a historical perspective. It outlines how that role has changed over the past hundred years and discusses the forces that have promoted the changes. In the period between 1913 and 1980, there was a large increase in public spending in industrial countries and a considerable expansion in the role of the government in the economy in all countries. The paper also outlines the intellectual developments that, starting in the 1970s, have brought about a reaction to the large role that the state has come to play in the economy.